EFFECT OF DIFFERENT VISUAL IMPAIRMENT LEVELS ON THE QUALITY OF LIFE IN GLAUCOMA PATIENTS - Runjić, Tina (Acta Clin Croat, 2018)
SUMMARY – The aim of this study was to assess the effect of different visual impairment levels on difference in the subjective quality of life estimation. We included 150 patients with glaucoma whose best-corrected visual acuity in the better-seeing eye was 0.5 and less. All of them were in advanced stage of the disease, with visual field defect worse than 12 dB in mean defect, when measured with the Octopus Visual Field Analyzer. In order to assess the quality of life, we used the Impact of Vision Impairment questionnaire. Additionally, we used General Information Questionnaire, which was developed for the purpose of this study. The information obtained from the questionnaires was analyzed using the Robust Discriminant Analysis program. Difference analysis was performed for each of the three areas of the questionnaire (reading and accessing information, mobility and independence, and emotional well-being). Results of this study confirmed the difference between the groups of patients with different levels of visual impairment, varying from total visual loss up to visual acuity 0.5 on the better-seeing eye in the effects of visual impairment on the quality of life. All levels of visual impairment had the largest effect in the area of reading and accessing information, slightly less in the area of mobility and independence, and the least effect was in the area of emotional well-being. Based on the results, it is concluded that all levels of visual impairment have negative effect on the quality of life in glaucoma patients.